Outcomes of Pediatric Kidney Transplantation in Recipients of a Previous Non‐Renal Solid Organ Transplant. Issue 7 (30th March 2017) - Hamdani, G.; Zhang, B.; Liu, C.; Goebel, J.; Zhang, Y.; Nehus, E.
Abstract : Children who receive a non‐renal solid organ transplant may develop secondary renal failure requiring kidney transplantation. We investigated outcomes of 165 pediatric kidney transplant recipients who previously received a heart, lung, or liver transplant using data from 1988 to 2012 reported to the United Network for Organ Sharing. Patient and allograft survival were compared with 330 matched primary kidney transplant (PKT) recipients. Kidney transplantation after solid organ transplant (KASOT) recipients experienced similar allograft survival: 5‐ and 10‐year graft survival was 78% and 60% in KASOT recipients, compared to 80% and 61% in PKT recipients (p = 0.69). However, KASOT recipients demonstrated worse 10‐year patient survival (75% KASOT vs. 97% PKT, p < 0.001). Competing risks analysis indicated that KASOT recipients more often experienced graft loss due to patient death (p < 0.001), whereas allograft failure per se was more common in PKT recipients (p = 0.01). To study more recent outcomes, kidney transplants performed from 2006 to 2012 were separately investigated. Since 2006, KASOT and PKT recipients had similar 5‐year graft survival (82% KASOT vs. 83% PKT, p = 0.48), although 5‐year patient survival of KASOT recipients remained inferior (90% KASOT vs. 98% PKT, p < 0.001). We conclude that despite decreased patient survival, kidney allograft outcomes in pediatric KASOT recipients are comparable to those of PKT recipients. Abstract : In pediatric kidney transplant recipients who previously received a non‐renal solid organ transplant, kidney allograft survival is comparable to primary kidney transplant recipients.